Ecological assessment and forecasting of surface water conditions in the Southern Bug River in the territory of Mykolaiv region - Horoshkovа, Lidiia; Menshov, Oleksandr; Nekos, Alla; Korniichuk, Yuliia; Horoshkov, Stanislav; Kochanov, Eduard (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. The issue of water supply and water security has become more relevant in the territory of Ukraine under conditions of war. Taking into account that Ukraine has an extensive water infrastructure, which includes large multipurpose reservoirs, hydroelectric power station dams, cooling systems for nuclear power plants, and others, the impact of the war is already environmentally hazardous and catastrophic. That is why research into anthropogenic influence, including during military actions, is relevant for the Southern Bug River, which is an important strategic resource for the ecological, social, and economic development of the Mykolaiv region of Ukraine.The purpose of article. Assessment of anthropogenic and military impact on the surface waters of the Southern Bug River within the Mykolaiv region, which are used for drinking water supply, in order to forecast the development of the ecological situation and to form measures for its improvement at the stage of post-war recovery of the country.Research methods. Methods of comparison, computer-based statistical data processing using correlation analysis of the results, as well as modeling and forecasting using regression analysis, were applied.Research results. The paper presents the results of studies on the impact of anthropogenic and military pressure on the ecological state of surface waters within the Mykolaiv region, namely the Southern Bug River, at 153 km, near the village of Oleksiivka (village of Pankratove), drinking water intake of the city of Yuzhnoukrainsk, Mykolaiv region (47°86′87″ N, 31°11′97″ E). A forecast of the level of anthropogenic load from key pollutants was carried out using regression equations, and projected levels of phosphate ions, ammonium ions, sulfate ions, chloride ions, BOD₅, and dissolved oxygen in the surface waters of the Southern Bug River were determined.Conclusions. The study presents the results of a comprehensive ecological assessment of the quality of surface waters of the Southern Bug River in the city of Yuzhnoukrainsk, Mykolaiv region, over the period of 2003–2024. The dynamics of key water quality indicators were studied, in particular the content of phosphate ions, ammonium, sulfate ions, chloride ions, biochemical oxygen demand (BOD₅), and the level of dissolved oxygen. The obtained analysis results allow us to conclude that the aquatic system of the Southern Bug River in the area of Oleksiivka (Pankratove) has a stable biogenic-organic load, which intensified during 2020–2024. An increase in nitrogen, phosphates, surfactants, and herbicides indicates a systematic influence of domestic and agricultural pollution sources. The trends in COD/BOD₅, combined with a decrease in dissolved oxygen, indicate a decline in aeration potential and an increased risk of hypoxia. A forecast of the anthropogenic load level from key pollutants was carried out using regression equations, and projected levels of phosphate ions, ammonium ions, sulfate ions, chloride ions, BOD₅, and dissolved oxygen in the surface waters of the Southern Bug River were determined.